Power Generation Enhancement by Utilizing Plant Photosynthate in Microbial Fuel Cell Coupled Constructed Wetland System - Shentan Liu; Hailiang Song; Xianning Li; Fei Yang (International Journal of Photoenergy)
In the present study, a new technology that coupled constructed wetland (CW) with microbial fuel cell (MFC) (CW-MFC) was developed to convert solar energy into electricity on the principles of photosynthetic MFC by utilizing root exudates of Ipomoea aquatica as part of fuel. The maximum power density of 12.42 mW m−2 produced from the CW-MFC planted with Ipomoea aquatica was 142% higher than that of 5.13 mW m−2 obtained from the unplanted CW-MFC. The maximum power output for the planted CW-MFC could be divided into two parts: the maximum power yield from in the water body was 66.05 KJ Kg−1  , and the maximum power transformation from plant photosynthesis was 2.31 GJ ha−1 year−1. The average COD removal efficiencies were 92.1% and 94.8% in the unplanted CW-MFC and planted CW-MFC, respectively; the average TN removal efficiencies amounted to 54.4% and 90.8% in the unplanted CW-MFC and planted CW-MFC. This research demonstrates that planting Ipomoea aquatica in the CW-MFC achieved a higher power density and nutrient removal of nitrogen simultaneously.